Appreciation and Characteristics of Offering Dance as Traditional Culture for Riau Society - Sari, Maya Novita; Indrayuda, Indrayuda (Master Program of Social Science Education of Universitas Negeri Padang, Indonesia, 2025)
The appreciation of dance is closely related to the unique characteristics of each dance. Through the appreciation of dance, individuals can understand and value the various aspects that shape the identity of a dance, such as movement, emotional expression, and the cultural and historical context behind it. By deepening their understanding of the characteristics of dance, one can better appreciate the beauty and complexity of each dance performance witnessed. This article will examine the forms of appreciation and characteristics of performance dance, which include the essential elements of dance composition such as dance movements, floor design, music or accompaniment, dramatic design, themes, make-up and costumes, venue, and dance equipment. These nine components will serve as the main reference in analysing the appreciation and characteristics of performance dance as a new traditional culture of the Riau community. The appreciation of dance art towards performance dance as a manifestation of new traditional dance becomes a window that opens new horizons in understanding and appreciating the beauty and complexity of performing arts.